Re-visiting D-dimers and fibrin degradation products for the diagnosis of acute aortic dissection - Luo, Chwan-Yau; Roan, Jun-Neng (Journal of Thoracic Disease; Vol 9, No 7 (July 31, 2017): Journal of Thoracic Disease, 2017)
Acute aortic dissection (AAD), the most severe form of acute aortic syndrome, is a catastrophic condition and a challenge to physicians (1).